THE INFLUENCE OF SOME TECHNOLOGICAL PARAMETERS OF THE DAIRY PRODUCTS FABRICATION ON THE COLLOID ZINC COMPLEX STABILITY - Andrey Vladimirovich Blinov; Alexander Vladimirovich Serov; Alexey Alexeyevich Gvozdenko; Elena Vladimirovna Momot (Современная наука и инновации)
In our country, the problem of normalizing the intake of essential trace elements of zinc into the human body is quite urgent, the solution of which is the enrichment of affordable mass consumption products, an important place among which is milk and dairy products. This work is aimed at studying the influence of some technological parameters of dairy production on the stability of the colloidal complex of zinc.